Pertanggungjawaban Terhadap Wanprestasi Pada Bank Garansi Terkait Peran Notaris (Kasus Putusan Nomor 214/Pdt.G/2016/PN Pbr) - Isma, Anggun; Purnama Jelita, Tiara; Nurul Arizti, Dwitri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
A bank guarantee is a financial facility provided by banks to clients to ensure the fulfillment of contractual obligations. This service is regulated by the Indonesian Civil Code (KUHPer) Articles 1820-1850 and Bank Indonesia Regulation No. 23/88/KEP/DIR of 1991. Bank guarantees are typically used in construction projects to protect project owners from default risks by contractors. If a contractor fails to meet obligations, the bank assumes responsibility, provided that the contractor offers collateral equal to the guarantee’s value. This paper analyzes the responsibilities of parties involved in default cases related to bank guarantees, focusing on Case No. 214/Pdt.G/2016/PN Pbr. The dispute was filed by PT. Mawatindo Road Construction against the Ministry of Research, Technology, and Higher Education of Riau University concerning the construction of Building B of the University’s Teaching Hospital. The conflict arose when the contractor requested a project extension under Presidential Regulation No. 4 of 2015, but the request was denied, and the contract was unilaterally terminated by the defendant. The role of a notary in drafting bank guarantee deeds is crucial to ensuring legal certainty. According to Article 15 of Law No. 2 of 2014 on the Notary Position, a notary is responsible for creating authentic deeds that bind parties. However, a notary is not liable for defaults committed by the parties in the agreement. The notary’s responsibility is limited to ensuring the validity of documents and providing legal advice on contract clauses. In conclusion, bank guarantees function as a risk protection mechanism against defaults. However, the primary responsibility for fulfilling agreements lies with the parties involved, not the notary. Therefore, it is essential for all parties to adhere to legal provisions when drafting agreements to avoid future disputes.